Norway: Wilkins-Hearst Antarctic Expedition 1928-29, men on deck and pack ice - Wilkins, George H. (George Hubert), Sir, 1888-1958 (1928)
Wilkins-Hearst Antarctic Expedition 1928-29. Schlossbach and Myers on deck. Showing pack ice.